(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: AKI is a common clinical condition and is associated with increased mortality and morbidity and sepsis is the most common contributing factor to AKI. There is lack of study focused on characteristics differences between septic and non-septic AKI patients and clinical outcome in our setting. The aim of the study is to describe and compare the characteristics and clinical outcomes of patients with septic and non-septic AKI. Materials and methods: This was hospital based prospective cohort study carried out in the Department of Nephrology of CMCH, from March 2019 to February 2020. A total 94 patients of AKI diagnosed by The KDIGO AKI creatinine criteria, were enrolled in the study after following inclusion and exclusion criteria and divided into two groups- septic and non-septic AKI patients. Patients were followed till 90 days from admission. Demographics, clinical characteristics and outcome were analyzed. Results: Septic AKI was associated with worse clinical (Decreased MAP, increased mean HR, RR,) hematological (Higher mean WBC count, lower mean Hb%) and biochemical disturbance (Lower mean P H , HCO ). Septic AKI had significant association with Diabetes and NonSeptic AKI patients had significant association with HTN. Septic AKI patients had longer mean duration of 3 hospital stay and need more ICU admission. Septic AKI had more complete recovery of renal function than Nonseptic AKI (p=.010). Septic AKI had higher 90 days’ mortality rate compared with Non-Septic AKI (p=.047). Kaplan-Meier survival curves demonstrated reduced survival for patients with Septic AKI compared with NonSeptic AKI (p=.044). Conclusion: Significant differences were found in the characteristics and clinical outcome of patients with Septic AKI compared to Non-Septic AKI. Septic AKI was associated with worse clinical, hematological and biochemical disturbance. Patients with Septic AKI had longer duration of hospitalization, an increased risk of death and and showed trends toward greater renal function complete recovery within 3 months of follow up. JCMCTA 2023 ; 34 (2) : 118-124